Education and meaning. Approaches to a systematic review from logotherapy and existential analysis - Di Marco, María Elisa; Gottfried, Andrés Enzo; Difabio de Anglat, Hilda (Revista de Psicología, 2022)
The present paper aims to investigate, as a review of the background, the bibliography found in Spanish between the years 2000-2021 on education and meaning from the perspective provided by logotherapy and existential analysis. Given the lack of review studies on this topic, first, an expert consultation was held in order to identify main reference authors at the national—Argentina—and international level. Second, the literature review itself was carried out, following the guidelines of the PRISMA 2020 declaration. The following databases were consulted: Google Scholar, EBSCO, JSTOR, SciELO, Redalyc, DOAJ and Pubmed; then, based on the inclusion criteria, 60 publications were selected, which were systematized into four ordering categories. The results highlight an oversized category: the meaning of life in students.